Penggunaan Media Gambar untuk Meningkatkan Keterampilan Menulis Teks Narasi di Sekolah Dasar - Tiara Maharani; Vevy Liansari (Universitas Ngudi Waluyo, 2025)
Abstract This research aims to (1) determine the students' narrative text writing ability before using the image media, (2) determine the writing ability after the use of image media, and (3) test the effectiveness of picture media in improving the ability to write narrative narrative text. The research was conducted with a quantitative approach using one-group pretest-posttest design. The research subjects consisted of 38 students The instruments used were tests and assessment rubrics, while data analysis was done through the t-test. There was an increase in scores in all aspects of the assessment-including content organization, organization essay content, and language use-with the highest increase in the aspect of content organization. The t test resulted in a calculated t value of -7.246 which is greater than the t table of -2.02. greater than the t table of -2.026 at the 5% significance level, indicating a significant difference between the pretest and t table scores. significant difference between the pretest and posttest scores. Thus, image media proved to be effective in improving the ability to write narrative texts. elementary school students. Abstrak Penelitian ini bertujuan untuk (1) mengetahui kemampuan menulis teks narasi siswa sebelum menggunakan media gambar, (2) mengetahui kemampuan menulis setelah penggunaan media gambar, dan (3) menguji efektivitas media gambar dalam meningkatkan kemampuan menulis teks narasi. Penelitian dilakukan dengan pendekatan kuantitatif menggunakan desain one-group pretest-posttest. Subjek penelitian terdiri dari 38 siswa kelas IV SD Wunut 1. Instrumen yang digunakan berupa tes dan rubrik penilaian, sedangkan analisis data dilakukan melalui uji t. Hasil penelitian menunjukkan adanya peningkatan skor pada seluruh aspek penilaian—meliputi isi, organisasi isi karangan, dan penggunaan bahasa—dengan peningkatan tertinggi pada aspek organisasi isi. Uji t menghasilkan nilai t hitung sebesar -7,246 yang lebih besar dari t tabel sebesar -2,026 pada taraf signifikansi 5%, yang menunjukkan adanya perbedaan signifikan antara skor pretest dan posttest. Dengan demikian, media gambar terbukti efektif dalam meningkatkan kemampuan menulis teks narasi siswa sekolah dasar.